Farmers’ perception of adoption of postharvest technologies of selected food crops in rivers state, Nigeria (International Journal of Agricultural Research, Innovation and Technology, 2018)
The study was conducted to determine the perception of food crops farmers on adoption of selected post-harvest technologies in Rivers State, Nigeria. A multistage snow-ball, procedure was used to sample 135 selected food crops farmers in the State. A well, structured questionnaire was used to obtain information from the respondents using both descriptive and inferential statistical tools. The result revealed that, majority (85.9%) of the respondents, were females while 84.4% of the respondents were married. The mean age of the respondent was 41.0 years and highly experienced in food crops production with mean of 15.9 years experience. Majority of the respondents (77%) attended primary school. The level of food crops farmers’ perception on adoption of post-harvest technologies packages was positive, majority (78.1%) of the respondents agreed with the positive statements on adoption of post-harvest technologies, implying the possibility of high level of adoption of post-harvest technologies. The perception of the food crops farmers also had influence on adoption level of the selected post-harvest technologies packages with (P < 0.05). The study concluded that food crops farmers had positive perception of post-harvest technologies in the study area and the study therefore, recommends that Extension should make the technologies available along with training.Int. J. Agril. Res. Innov. & Tech. 7 (2): 22-26, December, 2017